Comparative Study of the Genetic Barriers and Pathways towards Resistance of Selective Inhibitors of Hepatitis C Virus Replication - Delang, Leen (American Society for Microbiology, 2011)
Hepatitis C virus (HCV) inhibitors include direct-acting antivirals (DAAs) such as NS3 serine protease inhibitors, nucleoside and nonnucleoside polymerase inhibitors, and host-targeting antivirals (HTAs) such as cyclophilin inhibitors that have been developed in recent years. Drug-resistant HCV variants have been reported both in vitro and in the clinical setting for most classes of drugs. We report a comparative study in which the genetic barrier to drug resistance of a representative selection of these inhibitors is evaluated employing a number of resistance selection protocols. The NS3 protease inhibitors VX-950 and BILN 2061, the nucleoside polymerase inhibitor 2′-C-methylcytidine, three nonnucleoside polymerase inhibitors (thiophene carboxylic acid, benzimidazole, and benzothiadiazine), and DEB025 were included. For each drug and passage in the selection process, the phenotype and genotype of the drug-resistant replicon were determined. For a number of molecules (BILN 2061 and nonnucleoside inhibitors), drug-resistant variants were readily selected when wild-type replicon-containing cells were directly cultured in the presence of high concentrations of the inhibitor. Resistance to DEB025 could be selected only following a lengthy stepwise selection procedure. For some DAAs, the signature mutations that emerged under inhibitor pressure differed depending on the selection protocol that was employed. Replication fitness of resistant mutants revealed that the C445F mutation in the RNA-dependent RNA polymerase can restore loss of fitness caused by a number of unfit resistance mutations. These data provide important insights into the various pathways leading to drug resistance and allow a direct comparison of the genetic barriers of various HCV drugs.